Studi Ketahanan Struktur Bangunan Hotel Eksisting Terhadap Beban Gempa Dengan Metode Berbasis Kinerja - Meilinda dewi; Lintang Enggartiasto (Journal of Innovative and Creativity, 2025)
Indonesia is a high-seismic region, which requires a comprehensive seismic design of building structures. Therefore, performance-based design is used to estimate the level of structural performance against seismic loading. The study discusses the structural resistance to strong earthquake loads in an existing building constructed of conventional reinforced concrete materials and has a residential function with a special moment frame system. The structural performance analysis procedure uses linear dynamic response spectrum and nonlinear displacement procedures in accordance with SNI1726-2019 provisions. The structural performance results using linear dynamic method show that the structure is safe against interstory drift and P-delta effects with mass participation and shear forces in compliance. Push-over analysis results indicate that this structure can withstand a 2,500-year return period with moderate damage.